2018
DOI: 10.1016/j.ejmg.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic commonalities between spinal muscular atrophy and amyotrophic lateral sclerosis: Converging roads to therapeutic development

Abstract: Spinal muscular atrophy (SMA) and amyotrophic lateral sclerosis (ALS) are the two most common motoneuron disorders, which share typical pathological hallmarks while remaining genetically distinct. Indeed, SMA is caused by deletions or mutations in the survival motor neuron 1 (SMN1) gene whilst ALS, albeit being mostly sporadic, can also be caused by mutations within genes, including superoxide dismutase 1 (SOD1), Fused in Sarcoma (FUS), TAR DNA-binding protein 43 (TDP-43) and chromosome 9 open reading frame 72… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 207 publications
0
29
0
Order By: Relevance
“…Skeletal muscle with reduced levels of SMN displays both cell-autonomous and non-autonomous defects [16,17] and is therefore an important therapeutic target for SMA. We have recently demonstrated the dysregulated expression of the transcription factor Krüppel-like factor 15 (Klf15) in skeletal muscle of SMA mice during disease progression [18].…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal muscle with reduced levels of SMN displays both cell-autonomous and non-autonomous defects [16,17] and is therefore an important therapeutic target for SMA. We have recently demonstrated the dysregulated expression of the transcription factor Krüppel-like factor 15 (Klf15) in skeletal muscle of SMA mice during disease progression [18].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that a series of genetic mutations are associated with ALS [ 172 , 173 ]. Mutations such as the Cu/Zn-dependent superoxide dismutase 1 (SOD1) gene caused loss of dynein function, leading to the accumulation of pathological protein aggregates in ALS [ 174 , 175 , 176 , 177 ]. Studies have shown that genetic mutations enhanced the binding of autophagy matrix to autophagosomes through interaction with LC3 [ 178 , 179 , 180 ].…”
Section: Autophagy and Nddsmentioning
confidence: 99%
“…1J), we sought to identify the causes of the swimming and paralysis phenotypes. We have shown in previous work that neurotransmission is affected in C. elegans models of ALS, and since ALS and SMA are very similar clinically (22) we tested synaptic function in smn-1(gk) animals. Upon treatment with aldicarb, an acetylcholinesterase inhibitor (23), smn-1 mutant worms displayed a hypersensitivity and paralyzed sooner than control animals, but not to the extent of unc-47(e307) positive control animals ( Fig.…”
Section: Disease Models and Mechanisms • Dmm • Accepted Manuscriptmentioning
confidence: 99%